Research of the broken roof structure and supporting capacity of a shield in a deep and thick coal seam - Li, Yang; Ou, Xiangji; Ren, Yuqi; Wang, Nan; Lei, Xinghai; Jin, Xiangyang (Frontiers in Earth Science, 2022)
We determine the key issues of the reasonable supporting capacity of a shield and the shield selection in the panel face in a deep and thick coal seam. The No.232204 panel face of the Meihuajing mine in the Yuanyanghu mining area is taken as the research background. Using theoretical analysis, numerical simulation, and field measurement, the fracture characteristics and instability forms of roof structure of the panel face were studied. A mechanical model of roof fracture structure was established to calculate the reasonable supporting capacity of the shield, which guided the shield selection for the panel face. Also, a calculation and analysis system of the supporting capacity of the shield in a deep and thick coal seam was developed to realize the dynamic calculation and analysis of the supporting capacity of the shield. The results are as follows. 1) when the first weighting of the main roof appears, the broken rock block is hinged to form a “three-hinged arch” balanced structure. When the periodic weighting of the main roof appears, the broken rock block forms a “voussoir beam” balance structure. Also, the supporting capacity of the shield is stable between 8,900 and 9,600 kN. 2) The theoretical calculation showed that the supporting capacity of the shield in the No.232204 panel face was 9,581.04 kN, and the ZY10000/28/62D shield with supporting capacity of 10,000 kN is selected in the No.232204 panel face. 3) Through self-developed calculation software, the thickness and bulk density of the immediate roof had little influence on the supporting capacity of the shield, and the main roof thickness and bulk density have considerable influence on the supporting capacity of the shield. 4) The field measurement showed that the maximum supporting capacity of the shield in the panel face was distributed between 9,000 and 10,000 kN, which accounted for 77.58%. The loading utilization rate was more than 90%, and therefore the selected shield was reasonable. The research results provide a theoretical basis for the selection of shield supports for a deep buried and thick coal seam in the Yuanyanghu mining area.